2020
DOI: 10.1016/j.ssmph.2020.100624
|View full text |Cite
|
Sign up to set email alerts
|

“Life or death”: Experiences of insulin insecurity among adults with type 1 diabetes in the United States

Abstract: Objective Insulin access for people with diabetes is a growing public health concern and particularly important for people with type 1 diabetes (T1D) who depend on insulin for survival. However, few studies have examined the psychosocial contexts in which people with T1D confront, navigate, and attempt to resolve insulin access barriers (IABs). We conducted a qualitative study to: 1) describe factors affecting insulin access among adults with T1D, 2) characterize behavioral and emotional responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
(21 reference statements)
1
24
0
Order By: Relevance
“…Rationing is deeply problematic and there was a little debate regarding insulin’s effectiveness, with powerful descriptions of how it is lifesaving. Participants with type 1 diabetes in a previous study described insulin as “life or death” for them [ 36 ], but this analysis shows that the general public also appreciates the life-saving nature of insulin. We found little evidence of the stigma associated with being on insulin among people with type 1 diabetes, which has been reported in previous studies [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rationing is deeply problematic and there was a little debate regarding insulin’s effectiveness, with powerful descriptions of how it is lifesaving. Participants with type 1 diabetes in a previous study described insulin as “life or death” for them [ 36 ], but this analysis shows that the general public also appreciates the life-saving nature of insulin. We found little evidence of the stigma associated with being on insulin among people with type 1 diabetes, which has been reported in previous studies [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implications of high-cost insulin were far reaching. While tweets reporting bankruptcy, stealing, and homelessness associated with the cost of insulin may seem like extreme subjects to post on a public platform, a study in 2020 with individuals with type 1 diabetes in the United States corroborated these stories [ 36 ]. Approximately 39.2% of the patients struggling to afford their insulin do not tell their health care professionals [ 37 ], making Twitter a potential way of identifying patients in need.…”
Section: Discussionmentioning
confidence: 99%
“…Though there is evidence that the cost of insulin affects all age groups [ 4 ], we found that over half of the campaigns were developed for individuals in middle adulthood. Middle adulthood is a time of the greatest financial stability, yet living with diabetes can greatly impact finances, marriage/divorce, raising and launching children, living with bad credit, employment, or medical insurance coverage, or result in exiting the workforce [ 6 , 24 ]. Additionally, those in middle adulthood are less likely to qualify for federal or state insurance programs compared with children and older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin access and affordability are critical barriers to preventing acute and long-term diabetes complications, yet people with diabetes report lack of support and resources from health care providers, pharmaceutical companies, insurance companies, hospital systems, and pharmacies [ 6 ]. Consequently, some people with diabetes are turning to social media crowdfunding as an attempt to relieve financial stress and obtain insulin.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the U.S., the price of insulin and insulin analogues has increased exponentially over the past several decades. Today, monthly out-of-pocket costs for T1D patients can range between $75–2000 depending on insurance coverage and insulin requirements, making proper treatment inaccessible for some individuals [ 60 ]. With the life-long insulin replacement therapy required to treat T1D patients, alternative forms of treatment must be developed to address the growing cohort.…”
Section: Introductionmentioning
confidence: 99%